Researching enterprise development : action research on the cooperation between management and labour in Norway - Levin, Morten (Dialogues on work and innovation, 2002)
Researching Enterprise Development is written by the key researchers of a large Norwegian Action Research program on enterprise development (Enterprise Development 2000). This book tells the stories of how the seven participating modules were developed, created and sustained as Action Research activities. Based on these stories, reflection on a broader analysis of core issues of the program are given on the following topics: the processes within the program and changing models for leadership how research groups become proficient as action researchers local research as.